Análisis de la información científica de biomasa agrícola residual utilizada para remediación de aguas contaminadas por metales pesados. - Viteri Canchig, Juan Francisco (2020)
Today, heavy metal pollution has become one of the most significant environmental problems worldwide, due to untreated wastewater from mines and industrial factories, impacting rivers and impairing water quality by drastically affecting food security and public health of the population. The main objective of this research project was to analyze scientific information on the use of residual agricultural biomass as water remediators contaminated by heavy metals. The main objective of this research project was to analyze scientific information on the use of residual agricultural biomass as water remediators contaminated by heavy metals. The methodology used was analytical and descriptive, twenty-seven bibliographic sources, constituted as follows, were examined for the development of this research; twenty scientific articles of regional impact published in journals such as: International Journal of Environmental Pollution, Academic Journal Engineering, Colombian Journal of Biotechnology, Luna Azul Magazine among others and seven higher education theses disseminated in institutional repositories of Ecuador during the years 2009-2020, with this information a checklist was developed to determine whether the results of the selected studies were positive or negative. Information systematization was performed using a database with the help of the Access program; distributed according to the scientific rigor they represent. Statistical graphs were developed, taking into account the twenty-one bibliographic sources as the total sample size and in a skillful manner five questions were skilled according to the role of residual agricultural biomass in removing heavy metals in contaminated water; where the outstanding residual agricultural biomass of the studies carried out over the period of the estimated time was identified and in this way have information of high scientific relevance. The analyzed results of the most outstanding selected scientific bases; they made it possible to appreciate that, with the use of residual agricultural biomass, from citrus shells (Citrus Limonium, Citrus sinensis, Tamarindus indica, Citrus aurantium) they have a wider variety of heavy metal accumulation mechanisms, obtaining very efficient removal percentages, on the other hand, the biosorption of heavy metals using residual agricultural biomass is considered an accessible alternative due to its high efficiency and low cost, relative to the traditional methods applied. The results described in the research analyzed showed that the use of residual agricultural biomass has the ability to remove heavy metals in contaminated water.